Comparative Evaluation of Functional Outcomes in High Condylar Fractures Treated with Closed Methods with and without Temporomandibular Joint Arthrocentesis: A Research Protocol for a Randomised Controlled Trial - Sachindra Dubey; Nitin Bhola; Anchal Agarwal (Journal of Clinical and Diagnostic Research)
Introduction: Temporomandibular Disorders (TMD) encompass a range of conditions affecting the joint and surrounding structures, often resulting in pain, restricted movement, and dysfunction. Arthrocentesis involves the insertion of a single needle into the joint space, allowing for irrigation, lavage, and aspiration of the joint. The present procedure aims to alleviate symptoms, improve joint function, and promote healing by removing inflammatory mediators, debris, and adhesions from the joint space. Need of the study: Arthrocentesis offers several advantages over traditional techniques, including reduced trauma, quicker recovery times, and a decreased risk of complications. It has emerged as a valuable tool in the multidisciplinary approach to managing TMDs, offering patients a minimally invasive option to relieve their symptoms and restore jaw function. Hence, the present study will present the utility of arthrocentesis as an adjunct procedure to closed reduction in high condylar fractures, improving the functionality of the condyle, providing pain relief, increasing mouth opening and bite force, stabilising bilateral occlusion, and normalising excursive movements. Aim: To compare and evaluate the efficacy of closed reduction with or without arthrocentesis in patients with high condylar fractures regarding functional outcomes. Materials and Methods: A randomised controlled trial will be conducted at Siddharth Gupta Memorial Cancer Hospital, Sawangi, Wardha, Maharashtra, India, from September 2024 to May 2026, involving 10 patients. The protocol includes examining patients with suspected high condylar fractures, taking detailed case histories, performing clinical examinations focusing on the Temporomandibular Joint (TMJ), and recording preoperative measurements of mouth opening and pain levels using a Visual Analogue Scale (VAS). Patients with suspected fractures will undergo radiographic examinations, and those meeting the inclusion criteria will be included in the study after providing informed consent. Arthrocentesis will be performed using a specialised needle with two lumens, inlet and outlet bevels, and a silicone stopper for maximal insertion depth. Statistical analysis will be conducted using descriptive and inferential statistics, specifically the Chi-square test and Student’s paired and Unpaired t-tests, with p-value<0.05 considered significant.